Transanal penetrating injuries to the colon in children - Басілайшвілі, Юрій Валентинович; Сігаєв, Борис Євгеньович; Штикер, Станіслав Юрійович; Basylaishvili, Yu.; Sihaev, B.; Shtyker, S. (My University, 2018)
Traumatic injuries of the anorectal zone in children are rare. There are very few reports on this subject in the literature. Meanwhile, a pediatric surgeon can meet with wounds of the rectum penetrating into the abdominal cavity, which are extremely severe. Among all abdominal organs rectal injuries account for 1 - 5%, increasing the frequency up to 6,6% in fractures of the pelvis and to 19 % in gluteal region wounds. The rarest group of injuries to the colon is transanal wounds of the rectum, penetrating into the abdominal cavity without the perineal wound.
Keywords: tramsanal injuries; colon injuries